Increasing Public Expenditure Efficiency in Oil-rich Economies : A Proposal - Devarajan, Shantayanan; Le, Tuan Minh; Raballand, Gaël (2012)
This paper proposes that, to increase the efficiency of public spending in oil-rich economies, some or all of the oil revenues be transferred to citizens, and fiscal instruments such as taxation be used to finance public expenditures. The authors develop the case as follows. First, they confirm the well-known result that public-expenditure efficiency is lower in oil-rich countries compared with other developing countries. Second, they show that this efficiency gap is associated with differences in accountability to citizens of government's spending decisions. They find that various measures of accountability are systematically weaker in oil-rich countries. They attribute this difference to the fact that oil revenues typically accrue directly to the government, unlike tax revenues, which pass through the hands of citizens. Third, they show that, controlling for a number of factors, accountability is stronger in countries that rely more on direct taxation to finance public spending. They conclude that accountability, and hence public expenditure efficiency, can be increased by transferring oil revenues to citizens and then taxing them to finance public spending. The paper reviews existing schemes that redistribute oil revenues to the population, such as the Alaska Citizen Fund, to assess the feasibility of a modest proposal in African countries. The authors conclude that, while it may be difficult to implement such a proposal in existing oil producers, there is scope for introducing it in some of Africa's new oil producers.